KEPEMIMPINAN HEGEMONIK KASTA BRAHMANA TERHADAP KASTA SUDRA DALAM NOVEL TARIAN BUMI KARYA OKA RUSMINI - Zainal arifin (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
It--the research--was the result of cultural hegemony theory on theanalysis process by Antonio Gramsci on an novel ?óÔé¼?ôTarian Bumi?óÔé¼?Ø written byOka Rusmini. The objective of the research was form of hegemonicleadership brahmin caste to sudra caste on the novel entitled ?óÔé¼?ôTarianBumi?óÔé¼?Ø. This research was arranged to find those important elementshegemonic which were supported hegemony cultural theory, such as: kindsof consensus, government job descriptions, coopted civil society, organicintellectual, traditional intellectual, and the process of hegemony crisis itself.The research method of this thesis was descriptive and analysis method.It was used to describe the facts occurred on literature work, in this case wassocial facts in the novel entitled ?óÔé¼?ô Tarian Bumi?óÔé¼?Ø used to decide social levelswithin the texts. Those facts were used as textual proof which showed theposition of important elements on the hegemony cultural theories.It could be concluded that hegemonic leadership brahmin caste tosudra caste can be found on the novel entitled ?óÔé¼?ôTarian Bumi?óÔé¼?Ø by OkaRusmini. The first proof was the consensus used to control classes clash onBalinese social life. The next was the hegemonic class which controlledthose consensuses through mythes. The third was civil which were?óÔé¼?ôterkooptasi?óÔé¼?Ø through Sekehe dance. The forth was organic intellectual andtraditional intellectual which were delegated. The last was the hegemonycrisis occurred on the pasive revolution on ?óÔé¼?ôPatiwangi?óÔé¼?Ø sacred ritual doneby an actor on the novel.Key words: hegemonic, tarian bumi, classes clash, antonio gramsci.